Análisis jurídico de la declaratoria de unión de hecho en la ciudad de Ibarra en el periodo 2022 - Aulestia Andrade, Andrick Ismael (2024)
This study is focused on analyzing the legalization of de facto unions in Ibarra, Ecuador, using a qualitative research approach, normativist, socio-legal and analytical method to examine 40 cases of de facto unions processed in the Judicial Unit of Family, Women, Childhood and Adolescents and Adolescent Offenders based in the Ibarra Canton of the year 2022. Case study techniques and interviews with family judges and lawyers in free professional practice were used. The Constitution of Ecuador and the Civil Code recognize de facto unions, guaranteeing rights similar to marriage, including the formation of property companies. However, judicial practice reveals difficulties in demonstrating stable and monogamous cohabitation for two years, as required by law, particularly in post-mortem cases. The legislation allows the formalization of de facto unions at any time, the study of cases of de facto unions reveals significant challenges in their judicial recognition in Ecuador, despite the fact that the law grants rights similar to marriage, including the possession of property, Difficulties are faced such as the need for true evidence, especially in post-mortem cases, and administrative problems that can delay the processes and affect the rights of the parties.